Analisis Media Sosial Instagram Anies Baswedan sebagai Kampanye Politik Pilpres 2024 - Pamungkas, Rizqi Nandadita; Permadi, Didi; Florina, Ike Desi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore the role of Instagram in Anies Baswedan's political campaign ahead of the 2024 presidential election. The research method used is content analysis, research focuses on campaign messages and public interactions on the platform. The research results reflect positive support with high levels of community interaction, strengthening Anies' positive image. The campaign strategy, such as the tagline